Post-Cracking Shear Stiffness Model of Reinforced Concrete Beams - Kaiqi Zheng; Siwen Ni; Yaohui Zhang; Junxuan Gu; Mingming Gao; Yang Wei (Buildings, 2023)
Macro diagonal cracks can significantly reduce the stiffness of slender reinforced concrete (RC) beams, which results in excessive deflection compared with limitations from design specifications. To evaluate the post-cracking stiffness of slender RC beams with diagonal cracks, a shear degradation model that considers shear deformation is proposed. Based on the variable angle truss model, this study deduced the strut angle formula based on the minimum energy principle. Then, the relationship between the stirrup yielding shear stiffness and elastic shear stiffness was modeled. Finally, the calculation procedure was developed by quantifying the stiffness degradation tendency. The comparison between the experimental results of deflection and the proposed analytical method showed good agreement. Additionally, the proposed method can capture the full-range features of shear strain curves.